Research progress of oncolytic virus combined with PD-1/PD-L1 inhibitors - GAN Zi-ying, TANG Hui (Jichu yixue yu linchuang, 2022)
Oncolytic viruses are often used in combination with immune checkpoint inhibitors represented in two ways by programmed cell death 1/programmed cell death-Ligand 1 (PD-1/PD-L1). One is oncolytic virus combined with PD-1/PD-L1 inhibitors, which is modified by gene recombination and natural weak toxicity, and another one is oncolytic virus with gene recombination carrying PD-1/PD-L1 antibody gene.